Gambaran Hasil Pemeriksaan Sifilis pada Ibu Hamil di Rumah Sakit Wijayakusuma Purwokerto - Oksita Asri Widyayanti; Mazidah Noer Inayah; Esa Dhiandani; Nunuk Herowati (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Syphilis is a sexually transmitted disease caused by the bacteria Treponema pallidum. Syphilis is a resilient and systemic disease. Syphilis is passed on sexually by vaginal, anogenital, and orogenital contact. Non-sexual interactions, such as physical contact and blood transfusions, also remain possible. The disease can also spread vertically from mother to fetus (transplacental), resulting in congenital syphilis in the fetus. According to the Ministry of Health of the Republic Indonesia, there were 7055 new cases of syphilis in Indonesia during 2018. According to the latest data, 6% of pregnant mothers in Pekalongan possessed syphilis. Other studies found that 13% of pregnant mothers in Northern Halmahera were infected with T. pallidum or proved positive for syphilis. The number of cases of pregnant mothers suffering from syphilis encouraged the conduct of this study to figure out the features of pregnant mothers suffering from syphilis recognized at Wijayakusuma Hospital, Purwokerto, Banyumas. In this study, pregnant mothers were examined using the rapid test for syphilis. The findings revealed that 20 pregnant mothers were negative for T. pallidum or syphilis.